Invertebrates as webmasters in ecosystems (CABI, 2000)
The current understanding of invertebrates in terrestrial and terrestrially dominated (i.e. lower-order stream) ecosystems is reviewed and assessed. The book emphasizes the centrality of the activity of invertebrates (including arthropods, insects and nematodes), which influence ecosystem function far out of proportion to their physical mass in a wide range of situations, particularly at the interface between land and air (litter/soil), water and land (sediments) and in tree canopies and root/soil systems. Consisting of 16 chapters by authors from the USA, Canada, Europe and Australia, the book is essential reading for ecologists and invertebrate biologists.